An evaluation of the DEXLIFE 'self-selected' lifestyle intervention aimed at improving insulin sensitivity in people at risk of developing type 2 diabetes: study protocol for a randomised controlled trial. Issue 1 (December 2015) - O'Donoghue, Grainne; Kennedy, Aileen; Stig Andersen, Gregers; Durkan, Eoin; Thybo, Tanja; Sinnott, Margaret; Nolan, John; O'Gorman, Donal
Abstract Background With the global escalation of type 2 diabetes and evidence consistently showing that its onset can be prevented or delayed by changing lifestyle behaviours, there is an urgent need to translate practical, affordable and acceptable interventions from the research setting into the real world. One such approach to lifestyle interventions might be the introduction of a programme in which the individual is provided with choice and facilitated to 'self-select' an exercise programme. Previous research has shown that this is likely to be less resource intensive, an essential requirement for success outside the controlled research environment, while at the same time promoting positive responses relating to adherence, competence and self-efficacy, essential attributes for long-term success. Through a two-group parallel-randomised controlled trial, this study aims to assess the clinical and psychological impact of the DEXLIFE 'self-selected' lifestyle modification programme in adults at risk of developing type 2 diabetes. Methods/design A total of 360 subjects at risk of developing type 2 diabetes are randomly assigned in a 1:3 ratio to a control (n  = 90) or intervention arm (n  = 270). Randomization is stratified by age, sex and body mass index. The control arm receives general information on lifestyle and diabetes risk. The intervention group participate in a 12 week 'self-selected' supervised exercise training programme accompanied with dietary advice to improve food choices. Participants are given access to Dublin City University Sport (an on-campus gym) and asked to perform four exercise classes per week. Dublin City University Sport offers over 50 classes per week, many of which are medically supervised. If weight loss is indicated, reduction in total calorie intake by 600 kcal/day is advised. Common to all food plans is <10 % saturated fat intake, as well as a dietary fibre intake of >15 g/1000 kcal. Insulin sensitivity is the primary outcome measure. Secondary outcome measures include glucose function, fitness, body composition, anthropometrics, heart rate variability, lipid profiles, blood pressure, physical activity levels, dietary intake and quality of life. Discussion "Self-selected" lifestyle intervention has not previously been evaluated in type 2 diabetes prevention and if shown to be successful could be implemented in practice immediately. Trial registration Current Controlled Trials:ISRCTN66987085 .